AI tools such as ChatGPT will disrupt hydrology, too. Issue 3 (9th March 2023) - Halloran, Landon J. S.; Mhanna, Saeed; Brunner, Philip
Abstract: Since its public release in late 2022, the artificial intelligence (AI) tool ChatGPT has generated considerable excitement and consternation. Many scientists, including hydrologists, view this tool and others like it as threats, while others dismiss them as irrelevant distractions. Although the capability of this technology to 'do' hydrological research is lacking, AI tools like ChatGPT present significant opportunities—with caveats—for the hydrology community and deserve close inspection by all.